Craniofacial reconstruction and its socio-ethical implications. (2nd July 2016) - Johnson, Harold
ABSTRACT: Facial reconstruction uses the skull as a framework on which media are built up according to predetermined anatomical guidelines. The process is an amalgam of science and sculpture, and thus occupies a unique place within museums, forensic science, and anthropology. Yet it is necessary to cultivate among its experts a greater sensitivity to the ethical and social questions surrounding their work since such issues have not received adequate attention. This paper examines the racial implications behind reconstructing faces, the ethics of their curation in museum settings, and suggests new approaches to both.